Green Marketing in Action: How Brands Can Stand Out with Sustainability - Heriyanto (SAFE-Network, 2025)
As sustainability becomes a central concern in consumer decision-making and corporate responsibility, green marketing has emerged as a strategic approach for brands seeking to achieve market differentiation and long-term loyalty. This study explores how brands utilize green marketing to stand out through sustainability by employing a qualitative research design involving in-depth interviews with marketing and sustainability professionals across multiple industries. Thematic analysis revealed five critical dimensions: authenticity of green claims, integration of sustainability into brand values, consumer trust and skepticism, strategic differentiation, and implementation barriers. Findings suggest that authentic and transparent sustainability efforts enhance brand credibility and competitive positioning, while internal resistance, financial constraints, and the risk of greenwashing limit the impact of green initiatives. The research contributes to the understanding of how sustainability-oriented branding can be both a moral commitment and a strategic advantage in increasingly eco-conscious markets, offering practical insights for marketers and corporate leaders seeking to build resilient and ethically grounded brand identities.